Understanding and Modeling Academic Performance: A Theoretical Approach - HAMLIRI , Mouhcine; ERRACHIDI, Adil; Said, YOUSSEF (Revue du contrôle, de la comptabilité et de l’audit, 2025)
Performance is a concept frequently mentioned both in daily life and in professional settings. It has become an obligation for various actors, regardless of their fields of activity. Thus, the performance of public organizations is an issue that has generated extensive discussion, particularly in recent years, which have been marked by significant transformations in management tools and the institutional principles of governance for public entities. The improvement of performance in higher education institutions and the introduction of management tools derived from the private sector into the management of public institutions have led to the emergence of certain public management reforms grouped under the term “New Public Management.” This framework allows for the exploration of various factors influencing the organizational performance of universities. Through a literature review, this research article aims to analyze these determinants, highlighting the challenges and opportunities faced by educational institutions in their quest for efficiency and excellence.